2008
DOI: 10.4049/jimmunol.180.9.6392
|View full text |Cite
|
Sign up to set email alerts
|

Blocking NK Cell Inhibitory Self-Recognition Promotes Antibody-Dependent Cellular Cytotoxicity in a Model of Anti-Lymphoma Therapy

Abstract: Human NK cells lyse Ab-coated target cells through the process of Ab-dependent cellular cytotoxicity (ADCC). Improving ADCC responses is desirable because it is thought to be an important antitumor mechanism for some Abs. NK cell inhibitory receptors, such as killer cell Ig-like receptors, engage with MHC class I molecules on self-cells to block NK cell activation. Accordingly, we enhanced ADCC responses by blocking NK cell inhibitory receptors, thus perturbing induction of the self-recognition signal. In a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
145
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(152 citation statements)
references
References 70 publications
7
145
0
Order By: Relevance
“…Accordingly, potential therapeutic options have been proposed to enhance NK cell cytotoxicity by either reducing inhibitory signals or by enhancing stimulatory signals. Along this line, NK cell cytotoxicity against tumors was augmented by Ab-mediated masking of inhibitory receptors (36,37) or by using interfering RNA sequences that target transcripts for inhibitory receptors and downregulate their expression (38). Also increasing stimulatory signals led to enhanced cytotoxic activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, potential therapeutic options have been proposed to enhance NK cell cytotoxicity by either reducing inhibitory signals or by enhancing stimulatory signals. Along this line, NK cell cytotoxicity against tumors was augmented by Ab-mediated masking of inhibitory receptors (36,37) or by using interfering RNA sequences that target transcripts for inhibitory receptors and downregulate their expression (38). Also increasing stimulatory signals led to enhanced cytotoxic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Although the observed cytotoxic effects were lower in comparison with experiments performed in allogeneic settings, measurable cytotoxicity was induced. However, reduced efficiencies in such 3-to 4-h 51 Cr-release experiments in autologous settings are common and have been reported for rituximab and other CD20-specific Ab derivatives (27,36,46).…”
Section: Discussionmentioning
confidence: 99%
“…28,29 The expression levels of CD16a on the NK92/CD16a cells did not differ remarkably from those on NK cells in PBMCs isolated from healthy volunteers. For these reasons, the use of NK92/CD16a seemed to be appropriate for evaluating ADCC mediated by cetuximab.…”
Section: Discussionmentioning
confidence: 99%
“…For example, reducing inhibitory KIR function by specifically blocking ligand recognition would be particularly effective in treating patients with HLA-expressing tumors that are resistant to NK cell-mediated lysis. A recent report by Binyamin et al 124 demonstrated that antibody-mediated KIR blockade significantly augmented NK cell ADCC responses. However, blocking KIR alone did not significantly increase NK-mediated killing of autologous tumor cells in an in vitro study.…”
Section: Clinical Trials Of Nk Cell-mediated Tumor Immunotherapymentioning
confidence: 99%
“…108,122 Treating with Rituximab combined with an antibody that blocks inhibitory self-recognition or an immunomodulatory agent (Lenalidomide) that upregulates NK-cell activation markers enhanced NK cellmediated cell lysis. 123,124 NK cell lines Using NK cell lines as the source for therapeutic allogeneic NK cells may be potentially beneficial, as the lack of KIR ligand(s) (recognizing HLA) in the recipient induces NK-cell function. 125 Seven established malignant NK cell lines, including NK-92, YT, NKL, HANK-1, KHYG-1, NK-YS and NKG, have been previously reviewed by us.…”
Section: Allogeneic Nk Cellsmentioning
confidence: 99%